Psychiatric symptoms in Long-COVID patients: a systematic review - Marchi, Mattia; Grenzi, Pietro; Serafini, Valentina; Capoccia, Francesco; Rossi, Federico; Marrino, Patrizia; Pingani, Luca; Galeazzi, Gian Maria; Ferrari, Silvia (Frontiers in Psychiatry, 2023)
Objective People who have been infected by COVID-19 showing persistent symptoms after 4 weeks from recovery are thought to suffer from Long-COVID syndrome (LC). There is uncertainty on the clinical manifestations of LC. We undertook a systematic review to summarize the available evidence about the main psychiatric manifestations of LC. Method PubMed (Medline), Scopus, CINHAL, PsycINFO, and EMBASE were searched until May 2022. Studies reporting estimation of emerging psychiatric symptoms and/or psychiatric diagnoses among adult people with LC were included. Pooled prevalence for each psychiatric condition was calculated in absence of control groups to compare with. Results Thirty-three reports were included in the final selection, corresponding to 282,711 participants with LC. After 4 weeks from COVID-19 infection recovery, participants reported the following psychiatric symptoms: depression, anxiety, post-traumatic symptoms (PTS), cognitive and sleeping disturbances (i.e., insomnia or hypersomnia). The most common psychiatric manifestation resulted to be sleep disturbances, followed by depression, PTS, anxiety, and cognitive impairment (i.e., attention and memory deficits). However, some estimates were affected by important outlier effect played by one study. If study weight was not considered, the most reported condition was anxiety. Conclusions LC may have non-specific psychiatric manifestations. More research is needed to better define LC and to differentiate it from other post-infectious or post-hospitalization syndromes. Systematic review registration PROSPERO (CRD42022299408).